A short review on CRP synthesis inhibition in cardiovascular disease - Zaczkiewicz, Myron; Zimmermann, Oliver; Torzewski, Jan (Frontiers in Drug Discovery, 2024)
C-reactive Protein (CRP) is synthesized in the liver. Synthesis is stimulated via the IL-1ß/IL6 pathway. CRP activates the complement system via C1q and macrophages via Fc receptors. Since elevated CRP plasma levels are associated with increased cardiovascular risk, CRP may play a causal role in cardiovascular disease. One approach to transfer these observations into standard medical care would be to generate hepatic CRP synthesis inhibitors testing them in controlled clinical trials. Despite huge pharmacological efforts, the search for CRP synthesis inhibitors proved to be difficult. The antisense oligonucleotide RNA technology, although a promising idea, has not yet led to results feasible for clinical practice. High throughput screening assays in search for hepatic CRP inhibitors were limited by the fact that primary human hepatocytes do not adequately grow in vitro. Use of genetically engineered hepatoma cells led to the observation that cardiac glycosides are capable of inhibiting CRP synthesis. Because of patent law considerations, however, pharmaceutical companies had limited interest in pursuing this possible path. Upstream inhibition of IL-1ß and IL-6 by antibodies has shown positive results in cardiovascular clinical trials, but because of side effects none of these antibodies has yet received FDA approval. In contrast, long-term colchicine treatment, though not being a CRP-specific approach, has recently been approved by the FDA. Taken together, there is no evidence that hepatic CRP synthesis can specifically, effectively and safely be inhibited in vivo in human medicine. Here, we summarize contemporary approaches to inhibit CRP synthesis and potential goals for future clinical trials.